Changes in the Contraceptive Practice among the Women of Reproductive Age in a Selected Hospital of Dhaka City (Medicine Today, 2016)
Family planning is an essential tool for reducing fertility rate. An increase in contraceptive prevalence rate results in reduction of population growth, which in turn contributes significantly to the improvement of people's health. This is a cross-sectional, descriptive type of study carried out among the married women attending in the gynaeout patient department of MARKS Medical College and Hospital. This study was conducted from 1st June 2013 to 31st May 2014. Sample size was 250 which were selected purposively.Reproductive history was used as research instrument for data collection. Data was collected by face to face interview using structured questionnaire. Among 250 married women 156(62%) women practicing contraceptives. Majority 45.6% of the respondents were in the age group of 25-29 yrs. Among the respondents housewives 36%, service holder 64% and 38.4% were educated. About 42.8% respondents had 2 child followed by 3 children 36% & only 1.6% had 4 children. 100% respondents had knowledge about oral pill and barrier method. Among the contraceptive users 35.8% respondents accepted OCP followed by barrier method 33.3%, IUCD users were 16.7%, 7.7% respondents used injectables, 6.4% were natural method user and only 1.2% used emergency pills. Maximum 59% respondents were using contraceptives for less than one year, only 4.5% were using contraceptive of different methods for 10 years. Fertility rate, menstruation regulation is lower among servicing women. Education, empowerment and social position of women help to reduce fertility.Medicine Today 2015 Vol.27(2): 33-36